From dimming to brightening during 1961 to 2014 in the maize growing season of China. (6th February 2021) - Liu, Zhijuan; Yang, Xiaoguang; Lin, Xiaomao; Zhang, Zhentao; Sun, Shuang; Ye, Qing
Abstract: Climate patterns, cropping systems, and agricultural technologies have greater diversity among various regions in China. Knowledge of the spatial–temporal patterns of solar radiation during the maize growing season is essential for farmers and extension technicians in their optimization of cropping choices and development of adaptation strategies for climate change. In this study, based on the observed solar radiation in six subregions of China, we analyzed the spatial distributions and temporal trends of incident solar radiation ( SRi ), beam solar radiation ( SRb ), and diffuse solar radiation ( SRd ) during 1961–2014. From 1961 to 1984, the annual SRi in most areas showed a downward trend, with a median value of −27.8 MJ m −2  year −1, which is primarily due to a decrease in SRb . However, after 1985, 76% of locations had reversed to brightening. This finding is primarily due to an increase in SRd . The trends in SRi during the whole growing season (WGS) of maize changed by −12.4% to 18.3% during the past 30 years, and 74% of the selected locations showed an increasing trend. At most of the stations, SRb showed a decreasing trend during the WGS, and SRd showed an increasing trend. The trends of SRi, SRb, and SRd during the vegetative period and reproductive period of maize have generally followed a trend similar to the WGSs. Therefore, we conclude that annual solar radiation changed from dimming to brightening from 1961 to 2014 in China. Solar brightening occurred during the maize growing season, which was mainly caused by an increase in diffuse radiation. Abstract : Crop yields are affected by many factors related to breeding, management, and climate. Understanding climate factors trends and possible impacts on yield trend is important to help ensure that these yield increases continue in the future. So the scientific question in this paper we are addressing is how the changes of solar radiation during the maize growing season during the past 5 decades?